Effectiveness and safety of nivolumab in the treatment of lung cancer patients in France: preliminary results from the real-world EVIDENS study. (1st January 2020) - Barlesi, Fabrice; Dixmier, Adrien; Debieuvre, Didier; Raspaud, Christophe; Auliac, Jean-Bernard; Benoit, Nicolas; Bombaron, Pierre; Moro-Sibilot, Denis; Audigier-Valette, Clarisse; Asselain, Bernard; Egenod, Thomas; Rabeau, Audrey; et al.
ABSTRACT: EVIDENS is an ongoing, prospective, non-interventional study evaluating the effectiveness and safety of nivolumab in lung cancer patients in France (ClinicalTrials.gov NCT03382496). Adults with a pathologically confirmed diagnosis of lung cancer and initiating treatment with nivolumab were recruited from 146 sites in France. This analysis included only patients with non-small cell lung cancer (NSCLC) who received ≥1 nivolumab infusion, and evaluated patient characteristics at the time of nivolumab initiation and its effectiveness and safety after a median follow-up of 18 months. A total of 1, 420 patients with NSCLC were included, most of whom had an Eastern Cooperative Oncology Group performance status (ECOG PS) of 0–1 (82.9%), non-squamous histology (69.2%) and stage IV disease (91.4%). Brain metastases were present in 19.9% of patients. Nivolumab was a second-line or ≥third-line regimen in 73.6% and 26.1% of patients, respectively. Almost all patients had prior chemotherapy (99.7%). Median overall survival was 11.2 months (95% confidence interval [CI]: 10.0–12.4). ECOG PS, smoking status, corticosteroids at baseline, epidermal growth factor receptor mutation status, presence of symptomatic brain metastases and treatment-related adverse events (TRAEs) were independent predictors of survival. Grade 3 and 4 TRAEs were reported in 105 (7.4%) and 12 (0.8%) patients, respectively; no treatment-related deaths were reported. Preliminary results of the EVIDENS study confirm the effectiveness and safety of nivolumab, mostly in pre-treated advanced NSCLC patients, with similar benefits to those observed in the phase III randomized clinical trials, despite a broader study population.